Robust Control of Railway Traction System. Issue 25 (2018) - Dincel, Emre; Nak, Handan; Akkaya, Şirin; Canevi, Mehmet; Mutlu, İlhan; Söylemez, M. Turan
Abstract: In this paper, a robust control strategy of a railway traction system with induction motor is proposed. The control problem is divided into sub-loops such as, current loop, acceleration loop, speed loop and position loop. A conventional PI controller is designed for the current loop, which is a very fast loop in comparison to the other mechanical loops. A nonlinear PI controller is used to control the acceleration loop. The speed and position loops are controlled via robust PI-PD controllers. The robustness problem is considered both as disturbance rejection, which arise due to resistive forces, and as robustness against uncertainties such as, the mass of the railway vehicle and the wheel diameter. The practical applicability of the method is emphasized via verification and validation steps with realistic constraints on acceleration, jerk, torque and power on a case study. Simulation results reveal that the proposed controller structure is quite effective for a railway traction system.